2016
DOI: 10.1007/s00348-016-2120-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of afterbody rounding on the pressure distribution over a fastback vehicle

Abstract: International audienceExperimental analyzes were performed to understand the drag evolution and the flow field modifications resulting from afterbody rounding on the Ahmed body, a simplified vehicle model with 25 degrees rear slant. Curvature effects were investigated using balance measurements, flow visualizations, wall pressure, and particle image velocimetry measurements. The rear end of the original well-known Ahmed body has sharp connections between the roof and the rear window as well as squared rear pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 13 publications
(19 reference statements)
1
26
0
Order By: Relevance
“…The sharp side pillars force the lateral flow to separate, generating longitudinal vortices. As analyzed by the same authors, 6 it is suggested that for S 0 , the sharp lateral edges ''shield the wake separation region at the base and enable a ''two-dimensional separation, ''2D meaning that the mean streamlines at separation are more parallel to the orientation of the flow over the window, while longitudinal vorticity is concentrated in the C-pillar vortices. On the contrary, for rounded edges the flow is drawn in from the sides toward the center over the slanted surface.…”
Section: Base Geometry Flow Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…The sharp side pillars force the lateral flow to separate, generating longitudinal vortices. As analyzed by the same authors, 6 it is suggested that for S 0 , the sharp lateral edges ''shield the wake separation region at the base and enable a ''two-dimensional separation, ''2D meaning that the mean streamlines at separation are more parallel to the orientation of the flow over the window, while longitudinal vorticity is concentrated in the C-pillar vortices. On the contrary, for rounded edges the flow is drawn in from the sides toward the center over the slanted surface.…”
Section: Base Geometry Flow Analysismentioning
confidence: 96%
“…The high spanwise and vertical velocity associated to the transversal flow in S 40 , therefore, results in a global longitudinal rotation of the flow in the near wake. To quantify the rotation of the flow, the longitudinal evolution of the mean circulation GÃ = Ð SÃ O Ã x dS was analyzed as in the work of Rossitto et al 6 The domain of the calculation included all of the numerical domain presented in Figure 5. Despite the high levels of vorticity of the C-pillar vortices for S 0 , the overall circulation is higher for S 40 .…”
Section: Base Geometry Flow Analysismentioning
confidence: 99%
“…A similar study of the effect of the cargo door has recently been published in the slanted cylinder configuration by Bulathsinghala, Wang & Gursul (2019), who also observed the persistence of the vortical pair in the open configuration, although with decreased strength and increased unsteadiness levels. The effect of geometrical curvature has also been characterized in other highly three-dimensional bluff body wakes such as the Ahmed body (Rossitto et al 2016(Rossitto et al , 2017, where the addition of fillets at the trailing edges of the model led to increased vortex dissipation and drag reduction. However, comparisons regarding the level of unsteadiness of these flows and vortex wandering are still to be further characterized and understood.…”
mentioning
confidence: 99%
“…If the volume reduction is such that it does not preclude positioning inside the trailer of the pallet, this type of trailer shape changes could be easier to adopt from the transport community. Rossitto et al [14], show that aerodynamic lift forces for a fastback vehicle are largely affected by the rounding of the roof/backlight intersection. Other possible solution could be the "adding" of external passive devices to the trailer to reduce the side force.…”
Section: Introductionmentioning
confidence: 99%